1991
DOI: 10.1021/je00004a005
|View full text |Cite
|
Sign up to set email alerts
|

The N,N-dimethylformamide/ethane-1,2-diol solvent system. Density, viscosity, and excess molar volume at various temperatures

Abstract: Density (p), kinematic viscosity (p), and absolute viscosity ( ) are presented for mixtures of ethane-1,2-dlol and A/,A/-dimethylformamide from -10 to +80 °C. The above properties were fitted by empirical equations stating their dependence on temperature and mole fraction of the mixture. Furthermore, some considerations regarding the meaning of the obtained adjustment parameters are made. The excess functions, such as molar volumes VE, have been derived. The trends of V* data vs mole fraction of the mixtures h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
47
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 7 publications
7
47
1
Order By: Relevance
“…Viscosity values for pure glycols in the present work agree with the literature data [1, [3][4][5] within 10% except for those DEG obtained for DEG by Kumagai et al [~1] and, for TEG by Obermeier et al [3] as shown in Fig. 2.…”
Section: Resultssupporting
confidence: 92%
“…Viscosity values for pure glycols in the present work agree with the literature data [1, [3][4][5] within 10% except for those DEG obtained for DEG by Kumagai et al [~1] and, for TEG by Obermeier et al [3] as shown in Fig. 2.…”
Section: Resultssupporting
confidence: 92%
“…This work a Literature This work Literautre (47) 277 (48) 0.9466 (13) 298. 15 0.942915 0.943286 (49) 1.104264 1.104362 0.944061 (40) 0.945597 (48) 303.…”
Section: Densitiesmentioning
confidence: 99%
“…15 0.942915 0.943286 (49) 1.104264 1.104362 0.944061 (40) 0.945597 (48) 303. 15 0.938876 0.939376 (40) 1.103031 b 1.103142 0.940691 (48) 308. 15 0.933964 0.934402 (40) 1.101492 1.101631 0.935814 (48) 313.…”
Section: Densitiesmentioning
confidence: 99%
See 2 more Smart Citations